Diabetes-related foot disorders among adult Ghanaians. Issue 1 (1st January 2018) - Sarfo-Kantanka, Osei; Kyei, Ishmael; Mbanya, Jean Claude; Owusu-Ansah, Micheal
ABSTRACT: Background: Diabetic foot remains a challenge in most low-middle-income countries (LMICs). A severe deficit in data exists on them in sub-Saharan Africa (SSA). Up-to-date data on the longitudinal trajectories and determinants can provide a benchmark for reducing diabetic foot complications in SSA. Objective : The primary objective of this study was to estimate trends in the incidence of diabetic foot and determine predictors in an adult Ghanaian diabetes cohort. Design : The study is a retrospective longitudinal study over a 12 year period. Methods : We applied Poisson regression analysis and Cox proportional hazard models to demographic and clinical information obtained from patients who enrolled in a diabetes specialist clinic in Ghana from 2005 to 2016 to identify longitudinal trends in incidence and predictors of diabetic foot. Results : The study comprised 7383 patients (63.8% female, mean follow-up duration: 8.6 years). The mean incidence of foot disorders was 8.39% (5.27% males and 3.12% females). An increase in the incidence of diabetic foot ranging from 3.25% in 2005 to 12.57% in 2016, p  < 0.001, was determined. Diabetic foot, with adjusted hazard ratio (HR; 95% confidence interval (CI)), was predicted by disease duration, that is, for every 5-year increase in diabetes duration: 2.56 (1.41–3.06); male gender: 3.51 (1.41–3.06); increased body mass index (BMI), that is, for every 5 kg/m 2 : 3.20 (2.51–7.52); poor glycaemic control, that is, for every percentage increase in HbA1c: 1.11 (1.05–2.25), hypertension: 1.14 (1.12–3.21); nephropathy: 1.15 (1.12–3.21); and previous foot disorders: 3.24 (2.12–7.21). Conclusions : We have found a trend towards an increased incidence of diabetic foot in an outpatient tertiary diabetes setting in Ghana. Systemic and individual-level factors aimed at preventive foot screening as well as vascular risk factor control should be intensified in diabetic patients in Ghana and other LMICs. Abbreviations : BMI: Body Mass Index, BP: Blood Pressure, CI: Confidence Interval, HR: Hazard Ratio, HbA1c: Glycated Hemoglobin, PAD: Peripheral Arterial Disease, NCDs: Non Communicable Disease, SSA: Sub Saharan Africa.